Gestational weight gain disparities in South Carolina: Temporal trends, 2004‐2015. Issue 1 (28th July 2020) - Wende, Marilyn E.; Liu, Jihong; Mclain, Alexander C.; Wilcox, Sara
Abstract: Background: Few studies have examined secular trends in gestational weight gain (GWG) and findings are inconsistent. Parallel to increasing trends in pre‐pregnancy obesity, we hypothesised similar increasing GWG trends. Objectives: The study examined trends in GWG in South Carolina (SC), using methods to reduce bias. We also examined whether the 12‐year trends in GWG varied according to race/ethnicity and pre‐pregnancy weight. Methods: Data came from SC birth certificates, 2004 to 2015. We calculated standardised GWG z‐scores (GWGZ), using smoothed reference values to account for gestational age and pre‐pregnancy body mass index. Quantile regression was used to examine trends in GWGZ, adjusting for pre‐pregnancy weight status, race/ethnicity, parity, WIC participation, smoking during pregnancy, residence, age, and birth cohort. Results: Among 615 093 women, the mean GWGZ was −0.4 (SD = 1.3), which increased from −0.4 in 2004‐2005 to −0.2 in 2014‐2015. GWGZ increased at the 5th, 10th, 25th, 50th, and 75th percentiles (ranging 0.04 to 0.73 units), with differential trends observed in sub‐groups by pre‐pregnancy weight and racial/ethnic group. Notably, non‐Hispanic White women showed larger increasing trends (0.89 units) compared to non‐Hispanic Black (0.55 units) and Hispanic (0.76 units) women in the 5th percentile. Decreasing trends were seen overall for the 90th (−0.02) and 95th percentile (−0.06 units) but positive trends were not seen among women experiencing obese class 1 (no change in 90th and 95th), and 2 (0.01 units in 90th, −0.02 units in 95th). Conclusions: This study shows increasing GWGZ trends from the 5th to the 75th percentiles and decreasing trends in 90th and 95th percentiles in SC for the last decade. Racial/ethnic and pre‐pregnancy weight disparities did not improve over the study period. Future research is needed to confirm these findings in other states and to develop strategies to narrow racial and pre‐pregnancy weight disparities at the highest and lowest percentiles.